Status Anemi Ibu Hamil Trimester III Sebagai Efek Tingkat Kepatuhan Konsumsi Tablet Fe, Protein, Vitamin C dan Pengetahuannya - Arum, Dyah; Hutagalung, Sihol; Setiadi, Yuwono (Poltekkes Kemenkes Semarang, 2014)
BackgroundAnemia in pregnant women is still a big problem in Indonesia, and it can increase the mortality and morbidity of the mothers and babies. According to the Basic Health Research report 2007 showed that the prevalence of anemia in Central Java province reached 16.4 % and it is above the national prevalence of anemia 14.8 %. At the Mijen I health center 42,86% of 70 pregnant women were examined have haemoglobin less than 11g%Objective : To analyze the relationship between Fe tablet intake , protein ,vitamin C , and the knowledge, with the anemia status of third Trimester pregnant women..Method:The study was an observational analytic by using cross sectional approach. Held in December 2013 to January 2014. It is the total population of third trimester pregnant women that there are 44 pregnant women. Using The questionnaire which is consist of the identity of respondents, the level of knowledge. Fe tablet intake protein and vitamin C intake, recall 24 hours was done for two days, and photometer for measuring hemoglobin levels.Results : Fe tablet intake of respondents on average 56.8 % obedient, good protein intake as much as 59.1 % of respondents , majority of the respondents have less knowledge of the number 25 (56.8 %) of the respondents and the total of 61.4 % of respondents are not anemicConclusion: There is a significant relationship between adherences to consume Fe with maternal anemia status. There is a significant relationship between the level of protein intake with anemia status. There is a significant relationship between the consumption of Vitamin C it anemia status. There is a significant relationship between the levels of knowledge of the status of anemia